Analysis of the Interaction Network of Hub miRNAs-Hub Genes, Being Involved in Idiopathic Pulmonary Fibers and Its Emerging Role in Non-small Cell Lung Cancer - Yu, Dong Hu; Ruan, Xiao-Lan; Huang, Jing-Yu; Liu, Xiao-Ping; Ma, Hao-Li; Chen, Chen; Hu, Wei-Dong; Li, Sheng (Frontiers in Genetics, 2020)
Idiopathic pulmonary fibrosis (IPF) is a fibrotic interstitial lung disease with lesions confined to the lungs. To identify meaningful microRNA (miRNA) and gene modules related to the IPF progression, GSE32537 (RNA-sequencing data) and GSE32538 (miRNA-sequencing data) were downloaded and processed, and then weighted gene co-expression network analysis (WGCNA) was applied to construct gene co-expression networks and miRNA co-expression networks. GSE10667, GSE70866, and GSE27430 were used to make a reasonable validation for the results and evaluate the clinical significance of the genes and the miRNAs. Six hub genes (COL3A1, COL1A2, OGN, COL15A1, ASPN, and MXRA5) and seven hub miRNAs (hsa-let-7b-5p, hsa-miR-26a-5p, hsa-miR-25-3p, hsa-miR-29c-3p, hsa-let-7c-5p, hsa-miR-29b-3p, and hsa-miR-26b-5p) were clarified and validated. Meanwhile, iteration network of hub miRNAs-hub genes was constructed, and the emerging role of the network being involved in non-small cell lung cancer (NSCLC) was also analyzed by several webtools. The expression levels of hub genes were different between normal lung tissues and NSCLC tissues. Six genes (COL3A1, COL1A2, OGN, COL15A1, ASPN, and MXRA5) and three miRNAs (hsa-miR-29c-3p, hsa-let-7c-5p, and hsa-miR-29b-3p) were related to the survival time of lung adenocarcinoma (LUAD). The interaction network of hub miRNAs-hub genes might provide common mechanisms involving in IPF and NSCLC. More importantly, useful clues were provided for clinical treatment of both diseases based on novel molecular advances.